Bully Perpetration and Self-Esteem: Examining the Relation Over Time. (August 2017) - Rose, Chad A.; Slaten, Christopher D.; Preast, June L.
School-aged youth face a number of academic and behavioral challenges within the educational environment, including bullying involvement. Unfortunately, bullying has been linked to a number of detrimental psychosocial outcomes. Scholars have attempted to establish predictive profiles for youth involved in bullying. These profiles include bully perpetrators, where it has been argued that self-esteem is predictive of bullying behaviors. To address this association, the current study examined the relation between self-esteem and bully perpetration among 971 middle school youth through a longitudinal structural equation model. A three-step confirmatory factor analytic procedure determined that bully perpetration and self-esteem were metrically invariant and stable over time. The structural model suggested that bully perpetration at Time 1 predicted bully perpetration at Time 2, and self-esteem at Time 1 predicted self-esteem at Time 2. However, self-esteem at Time 1 did not predict bully perpetration at Time 2, and bully perpetration at Time 1 did not predict self-esteem at Time 2. These results suggest that students who engage in bully perpetration do not have higher or lower levels of self-esteem when compared with their peers who do not engage in bullying. Future research should continue to examine predictive factors associated with bully perpetration.